2015
DOI: 10.1039/c5gc00900f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of biologically active natural products, aspergillides A and B, entirely from biomass derived platform chemicals

Abstract: The synthesis of aspergillides A and B was achieved whereby all the carbon atoms originated from biomass derived platform chemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 85 publications
1
23
0
Order By: Relevance
“…Loh et al reported a synthetic route to natural products aspergillides A and B which exhibit potent cytotoxic activities towards mouse lymphocytic leukemia cell (Scheme 65). [197] In this route, all the carbon atoms in target molecules come from biomass-derived platform chemicals such as levulinic acid and HMF. The key steps in this synthesis were a oyori's asymmetric transfer hydrogenation to produce enantiopure alcohol 165 which was then subjected to an Achmatowicz rearrangement and subsequent reduction leading to pyranes 166 and 167, advanced intermediates in the preparation of the natural products aspergillides A and B.…”
Section: Scheme 64 Synthesis Of Furano-epothilone D From Hmfmentioning
confidence: 99%
“…Loh et al reported a synthetic route to natural products aspergillides A and B which exhibit potent cytotoxic activities towards mouse lymphocytic leukemia cell (Scheme 65). [197] In this route, all the carbon atoms in target molecules come from biomass-derived platform chemicals such as levulinic acid and HMF. The key steps in this synthesis were a oyori's asymmetric transfer hydrogenation to produce enantiopure alcohol 165 which was then subjected to an Achmatowicz rearrangement and subsequent reduction leading to pyranes 166 and 167, advanced intermediates in the preparation of the natural products aspergillides A and B.…”
Section: Scheme 64 Synthesis Of Furano-epothilone D From Hmfmentioning
confidence: 99%
“…A very interesting synthetic strategy for the preparation of biologically active compounds using exclusively biomass derived platform molecules has recently been reported by Koh et al 50 The authors described the syntheses of aspergilide A, B and C, three potent cytotoxic compounds, in which the main synthons for the backbone of the natural products are derived from HMF and levulinic acid ( Scheme 6 ). The multistep synthetic strategy includes among others the use of Noyori's asymmetric transfer hydrogenation, Achmatowicz rearrangement as well as an enzymatic kinetic resolution.…”
Section: Biomass Derived Chemical Space For the Synthesis Of Bio-actimentioning
confidence: 99%
“…[1] Given the ongoing depletion of these finite reserves, the development of biorefineries for organic chemical production will ensure as ustainable future for the chemical industry. [4] Some notable examples include the total synthesis of the cytotoxic aspergillides Aa nd B from biomass-derived platform chemicals [5] andt he emerging xylochemistry field. [4] Some notable examples include the total synthesis of the cytotoxic aspergillides Aa nd B from biomass-derived platform chemicals [5] andt he emerging xylochemistry field.…”
mentioning
confidence: 99%
“…[2] The incorporation of biomass-derived platform chemicals [3] into synthesis processes will have implications for the sustainable production of value-added products relevant to the fine and specialty chemicali ndustries;h owever,d espite the abundance of small molecules availablef rom biomass decomposition, their incorporation into multistep synthetic processes is relatively unexplored. [4] Some notable examples include the total synthesis of the cytotoxic aspergillides Aa nd B from biomass-derived platform chemicals [5] andt he emerging xylochemistry field. [6] In these ground breaking studies, the platformsa re all derived from cellulose and lignin.…”
mentioning
confidence: 99%